a) `ln ( ^3sqrt(x^4+12)/((x+16)sqrt(x-3)))`

`==> ln ((x^4+12)^(1/3) / ((x+16)(x-3)^(1/2)))`

`==> ln (x^4+12)^(1/3) - ln(x+16) - ln (x-3)^(1/2)`

`==> 1/3 ln (x^4+12) - ln (x^4+16) - 1/2 ln (x-3)`

``

`b) log_5 ((x^2(2+4x))^(3/2) / sqrt(x^3-x))`

`==> log_5 (((x^2)^(3/2) (2+4x)^(3/2))/(x^3-x)^(1/2))`

`==> log_5 (x^2)^(3/2) + log_5 (2+4x)^(3/2) - log_5 (x^3-x)^(1/2)`

`==>log_5 x^3 +3/2 log_5 (2+4x) - log_5 (x(x^2-1))^(1/2)`

`==> 3log_5 x + 3/2 log_5 (2+4x) - log_5 x^(1/2) - log_5 (x^2-1)^(1/2)`

`==> 3log_5 x + 3/2log_5 (2+4x) - 1/2 log_5 x - 1/2 log_5(x^2-1)`

`==> 5/2 log_5 x + 3/2log_5 (2+4x) - 1/2 log_5 (x^2-1)`

`==> (5log_5 x + 3log_5 (2+4x) - log_5 (x^2-1))/2`

``

``

``

``

``

``

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.